Análisis de los planes de atención de enfermería realizados por un grupo de estudiantes de la Facultad de Enfermería, de la Universidad de Antioquia, septiembre-noviembre, 1993 (1999)
ABSTRACT: The study and analysis about the attention plans of nursing done by nursing students in the internal medicine practice was done in order to prove if students have learned the attention process of nursing and its application to health care. It may be inferred that the nursing process, as a tool, is not systematically applied to the patient attention. Similar findings were found in a Venezuelan University by Rivas (1995). This fact allows us to reflect and rethink about nursing practices nowadays.